1986
DOI: 10.1111/j.1528-1157.1986.tb03536.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Lamotrigine (BW430C) in Persons With Epilepsy

Abstract: Sixteen epileptic patients took single doses of lamotrigine, 120 mg or 240 mg. Six photosensitive patients showed reduction (with abolition in two) in photosensitivity after lamotrigine administration. Five subjects with frequent interictal spikes showed reduction in spike frequency over 24 h after lamotrigine administration. The half-life (t1/2) of lamotrigine in subjects taking sodium valproate was prolonged, whereas the t1/2 in subjects taking carbamazepine and/or phenytoin was reduced. The area under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(87 citation statements)
references
References 11 publications
4
82
0
1
Order By: Relevance
“…Part of this variability may be accounted for by fluctuations in VPA c'oncentrations among patients taking the same dose (26). Significant increases in phenobarbital (PB) serum concentrations (22,27) and lamotrigine elimination half-life, both attributable to changes in hepatic metabolism, also have been documented with Concomitant administration of VPA (28).…”
Section: Discussionmentioning
confidence: 99%
“…Part of this variability may be accounted for by fluctuations in VPA c'oncentrations among patients taking the same dose (26). Significant increases in phenobarbital (PB) serum concentrations (22,27) and lamotrigine elimination half-life, both attributable to changes in hepatic metabolism, also have been documented with Concomitant administration of VPA (28).…”
Section: Discussionmentioning
confidence: 99%
“…progabide [1], lamotrigine [2], taltrimide, a taurine derivative [9], vigabatrine and loreclezole [11]. The experimental drug Org 6370 [8], however, has demonstrated paradoxical enhancement of photosensitivity with provocation of myoclonic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…This finding shows that absence of a PPR effect of a drug tested in only 1 dose should not be interpreted as evidence that the drug has no effect at all. CBZ is clearly a highly efficacious drug in patients with focal epilepsy, yet was either ineffective or poorly effective in this model at the standard dosage of 400 mg. A previous study by Binnie et al [4] reported that of 4 patients (3 with generalized seizures; 1 with partial onset seizures) treated with CBZ 400 mg doses (given as a liquid for rapid absorption), 2 had PPR abolishment. The study did not report serum levels [5] and it is unclear whether other factors, such as effects of concomitant AEDs, influenced CBZ responses.…”
Section: Discussionmentioning
confidence: 99%
“…If patients with a relatively stable IPS response are used as patients, studies can be performed using a study design that requires only 5-6 patients per dose tested. This protocol has been used to identify the antiepileptic effect of a number of AEDs (some now approved, some still in development), most notably levetiracetam (LEV), lamotrigine (LTG), brivaracetam, carisbamate, JZP4, YKP3089, and valproate (VPA) [1][2][3][4][5][6]. Drugs also have been tested that are sedatives, but not anticonvulsants, and these have failed to suppress photosensitivity [7], indicating that the assessment of PPR is both sensitive and specific.…”
Section: Introductionmentioning
confidence: 99%